Diagnosis, management, and treatment of a heritage-built environment in South Chile - Pizarro, Laura; Zumelzu, Antonio; Barría, Tirza; Prieto, Andrés J. (Journal of Civil Engineering and Management, 2025)
In Chile, photography arrived at the end of the 19th century together with the establishment of settlements of migrants from central Europe to southern Chile. The aims of this study are: (i) contextualise functional states of existing buildings in a specific sector of the historic Valdivia city centre; (ii) determine the state of conservation of the 42 cases under study; (iii) conduct qualitative and quantitative analyses of the main pathologies presented in the sample; (iv) perform an analysis focused on the urban context according to façade alignment, façade visibility index, and ratio of height versus street width; and (v) comparatively analyse the results achieved. This research reflects the importance of developing innovative procedures and mitigation strategies focused on preventive maintenance actions and future control systems that can maximise the resilience of a specific local context (Los Ríos region) and its surroundings. This study revealed that the number of pathologies detected was directly proportional to the state of conservation of the cases, classified by the functional service life model. Properties in Condition C were mainly affected by pathologies of a structural nature, which indicates that their functionality is not guaranteed, and a deeper inspection is needed for conservation and preservation actions. First published online 12 December 2024